Nudging Altruism by Color: Blue or Red? - Nie, Xinyu; Lin, Han; Tu, Juan; Fan, Jiahe; Wu, Pingping (Frontiers in Psychology, 2020)
Altruism, which is crucial to human beings and society, can be spontaneously aroused by environmental factors. The mechanism behind the influence on altruism remains debated. This research finds that different colors can alter the altruistic behaviors of people. Specifically, blue enhances altruism, whereas red functions conversely. We argue that different colors can simulate changes in information acquisition and then lead to the corresponding behaviors by using a process-tracing technique that monitors the selection of adaptive strategy. Results suggest that decision heuristic plays a mediating role in the link between colors and individual altruistic behaviors.